Setting the Stage for 2018: How the Changes in the American Joint Committee on Cancer/Union for International Cancer Control Cancer Staging Manual Eighth Edition Impact Radiologists - Glastonbury, C.M.; Mukherji, S.K.; O'Sullivan, B.; Lydiatt, W.M. (American Journal of Neuroradiology, 2017)
SUMMARY: The updated eighth edition of the Cancer Staging Manual of the American Joint Committee on Cancer will be implemented in January 2018. There are multiple changes to the head and neck section of the manual, which will be relevant to radiologists participating in multidisciplinary head and neck tumor boards and reading pretreatment head and neck cancer scans. Human papillomavirus–related/p16(+) oropharyngeal squamous cell carcinoma will now be staged separately; this change reflects the markedly better prognosis of these tumors compared with non-human papillomavirus/p16(−) oropharyngeal squamous cell carcinoma. Nodal staging has dramatically changed so that there are different tables for human papillomavirus/p16(+) oropharyngeal squamous cell carcinoma, Epstein-Barr virus–related nasopharyngeal carcinoma, and all other head and neck squamous cell carcinomas. Extranodal extension of tumor is a new clinical feature for this third staging group. In the oral cavity, the pathologically determined depth of tumor invasion is a new staging criterion, while extrinsic tongue muscle invasion is no longer part of staging. This review serves to educate radiologists on the eighth edition changes and their rationale.AJCCAmerican Joint Committee on CancercNclinical nodal stagingDOIdepth of invasionEBVEpstein-Barr virusENEextranodal extensionHNhead and neckHPVhuman papillomavirusNPCnasopharyngeal carcinomaOPSCCoropharyngeal squamous cell carcinomapNpathologic nodal stagingSCCsquamous cell carcinomaTNMtumor, node, metastasisUICCUnion for International Cancer Control